The use of historical evidence of the Tamiang kingdom on the east coast of Aceh as a source for learning local history for high school students - Usman, Usman; Akob, Bachtiar; Rahmatsyah, Rahmatsyah; Zakaria, Nurhijrah Binti (Universitas Negeri Malang, 2023)
The Tamiang Islamic Kingdom is one of the oldest kingdoms on the east coast of Aceh, bordering Haru Bay and Kampai Island of Pangkalan Susu. Its north serves as the front line of defense in the Malacca Strait, part of the sovereignty of the Samudra Pasai Islamic Kingdom, in the 12th century AD. In 1350, the country of Tamiang faced the challenge of the expansion of Majapahit commandeered by Patih Gaja Mada, who wanted to unite all regions in the archipelago following the